2021
DOI: 10.1177/21925682211008835
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Gelatin–Thrombin Matrix Sealant (Floseal®) for Reducing Blood Loss During Microendoscopic Decompression Surgery for Lumbar Spinal Canal Stenosis: A Retrospective Cohort Study

Abstract: Study Design: Retrospective cohort study. Objectives: To investigate the effectiveness and safety of a gelatin–thrombin matrix sealant (GTMS) during microendoscopic laminectomy (MEL) for lumbar spinal canal stenosis (LSCS). Methods: This study included 158 LSCS cases on hemostasis-affecting medication who underwent MEL by a single surgeon between September 2016 and August 2020. Patients were divided into 2 groups depending on whether GTMS was used (37 cases, Group A) or not (121 cases, Group B). Perioperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
9
2
Order By: Relevance
“…The study’s primary objective was to determine whether TCLH use during central stenosis or HNP with BESS is associated with a difference in the incidence of symptomatic and morphometric POSEH. In this study, the rates of symptomatic POSEH were 4.6% and 9.5% in groups A and B, respectively, which was higher than those in other studies [ 5 , 9 ]. In other studies, symptomatic POSEH cases were diagnosed only when severe paralysis occurred [ 5 , 9 ].…”
Section: Discussioncontrasting
confidence: 80%
“…The study’s primary objective was to determine whether TCLH use during central stenosis or HNP with BESS is associated with a difference in the incidence of symptomatic and morphometric POSEH. In this study, the rates of symptomatic POSEH were 4.6% and 9.5% in groups A and B, respectively, which was higher than those in other studies [ 5 , 9 ]. In other studies, symptomatic POSEH cases were diagnosed only when severe paralysis occurred [ 5 , 9 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Ma et al [28] found that Surgi o can signi cantly decrease intraoperative bleeding volume, total volume of intraoperative bleeding. Floseal differs from Surgi o in that it is prepared from bovine-derived gelatin crosslinked with methacrylic anhydride [20,24,29] . A retrospective analysis of the thousands of patient data was carried out by Ramirez et al [33] and found that Floseal can reduce transfusion requirements, bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [28] performed a RCT to explore the e cacy of Surgi o, and found that Surgi o could reduce blood loss in during hemostatic process in addition to the amount of blood loss, autologous blood transfusion and surgical time, and no adverse events are reported. Nomura et al [29] and Chen et al [30] Floseal could signi cantly decrease the intraoperative blood loss and postoperative drainage volume and did not increase the risks of adverse events. Therefore, the e cacy, especially in the safety of Floseal and Surgi o in spine surgery still remain unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies support the efficacy of GTMS across several surgical fields, [8][9][10][11][12][13][14] including spinal surgery. 15,16 Helenius et al 15 reported in their randomized clinical trial that GTMS could reduce intraoperative blood loss in patients undergoing posterior spinal fusion for AIS. However, the intervention was not blinded to the surgeons, and the trial was limited to experimental situations and rigorously conducted for all patients in the intervention group.…”
mentioning
confidence: 99%
“…Among them, gelatin-thrombin matrix sealant (GTMS) has become well-known in recent years owing to its relative ease of application and safety. Numerous studies support the efficacy of GTMS across several surgical fields, 8–14 including spinal surgery 15,16 . Helenius et al 15 reported in their randomized clinical trial that GTMS could reduce intraoperative blood loss in patients undergoing posterior spinal fusion for AIS.…”
mentioning
confidence: 99%